THE EFFECT OF REWARD SYSTEM AND WORK DISCIPLINE ON SALES PERFORMANCE OF PT. KARYA AGUNG MOTOR - Lona Chinsia Alfattama; Risma Ayu Novitasari (BEMJ : Business, Entrepreneurship, and Management Journal, 2024)
This research is motivated by the provision of a reward system and work discipline in sales. The reward system is very influential to motivate sales people to keep working hard. And discipline is also needed for the progress of the company. This research is quantitative research in which the data obtained through the process of distributing questionnaires and interviews. The results obtained from this study are that rewards have a significant effect on sales performance, work discipline has a significant effect on sales performance. The reward system and work discipline are the foundation and initial capital to work with in each individual as well as a trigger in increasing the productivity of sales people. To increase sales productivity, superiors provide rewards in the form of money/goods to sales people who succeed in achieving work targets and also impose sanctions on sales who violate disciplinary rules.